Thromboembolism after atrioventricular node ablation and pacing: long term follow up. Issue 4 (1st October 1999) - Gasparini, M; Mantica, M; Brignole, M; Gianfranchi, L; Menozzi, C; Pizzetti, F; Magenta, G; Delise, P; Proclemer, A; Tognarin, S; Ometto, R; Acquati, F; et al.
Abstract : OBJECTIVE: To assess the incidence of arterial embolic events in patients with high rate, drug resistant, severely symptomatic paroxysmal and chronic atrial fibrillation who have undergone atrioventricular (AV) node ablation and permanent pacing. DESIGN: Multicentre retrospective cohort study. PATIENTS AND MANAGEMENT: From May 1987 to January 1997, AV node ablation was performed in 585 severely symptomatic patients (mean (SD) age 66 (11) years) with high rate, drug resistant paroxysmal atrial fibrillation (308) or chronic atrial fibrillation (277). Lone atrial fibrillation was present in 133 patients, while the remaining 452 suffered from dilated, ischaemic, or valvar heart disease. Patients underwent VVIR (454) or DDDR (131) pacemaker implantation, after AV node ablation. Antiplatelet agents were given to 202 patients, warfarin to 187 patients. RESULTS: During a follow up of 33.6 (24.2) months, thromboembolic events were observed in 17 patients (3%); the actuarial occurrence rates of thromboembolism were 1.1%, 3%, 4.2%, and 7.4% after one, three, five, and seven years, respectively. Among five variables, univariate analysis showed that only the presence of chronic atrial fibrillation at the time of ablation (relative risk (RR) = 1.8, 95% confidence interval (CI) = 1.02 to 3.20, p = 0.04) and the need for warfarin treatment (RR = 1.6, 95% CI 1.00 to 2.71, p = 0.048) were associated with a significantly higher risk of occurrence of thromboembolic events. On multivariate analysis the only predictor of embolic events during the follow up was the presence of chronic atrial fibrillation. CONCLUSIONS: Data from this large cohort of patients indicate a fairly low incidence (1.04% per year) of thromboembolic events after AV node ablation and pacing for drug refractory, high rate atrial fibrillation.